Seroprevalence of hypodermosis in cattle in Nigde Province of Turkey by comparison of commercial and indirect-ELISA method - Karatepe, M.; Simsek, S.; Karatepe, B.; Cayvaz, M.; Sevgili, M.; Balkaya, I. (My University, 2013)
The aim of this study was to determine the seroprevalence of hypodermosis in cattle of Nigde province, located in the centre of Turkey. A total of 183 serum samples were collected between December 2009 and February 2010 for this goal. The serum samples were analyzed with a commercial ELISA kit (Pourquier ELISA Hypodermosis bovine serum screening) and an indirect-ELISA (using antigen Hypodermin C) methods. The results of the tests with the commercial ELISA kit showed that 53 (28.9%) out of the 183 cattle were seropositive for hypodermosis. Eleven (18.3%) out of the 60 female and 42 (34.1%) out of the 123 male, were found to be seropositive. The seropositivity rate was calculated as 21.8% (40/183) by indirect- ELISA, and the seroprevalence was 18.3% (11/60) and 23.5% (29/123) in female and males, respectively. A statistically significant correlation was observed when the two test methods for detecting seropositivity of Hypoderma were compared (p<0.001). This study is to the best of our knowledge the first serological survey on hypodermosis in cattle from the Nigde province of Turkey.
Keywords: Cattle; Enzyme-Linked Immunosorbent Assay (ELISA); Hypoderma spp.; Hypodermosis; Nigde; Seroprevalence; Turkey